Modern russian equipment for No‑Bake processes - Yu. N. Muravyov; A. V. Treshalin (Литьë и металлургия)
The article demonstrates the increasing trend of implementing the CHM technology in Russian foundries, highlighting the advantages of this technology and the equipment utilized. An analysis of the current market situation for foundry equipment supply is conducted, along with examples of modern Russian equipment produced by Rodonit company (St. Petersburg).